Massenrempulu Ethnicity from South Sulawesi in the Transformation of Political Identity and the Production of Cultural Differences (Faculty of Social Science, Universitas Negeri Semarang, 2022)
In the context of the political history of the kingdoms of South Sulawesi up to the end of the Dutch colonial period, Maspul was interpreted as a political alliance of small kingdoms in the mountainous region of South Sulawesi. the term Maspul is interpreted as an ethnic group among several more populous ethnic groups such as the Bugis, Makassar, Luwu, Toraja (South Sulawesi), and Mandar (West Sulawesi). This paper examines the phenomenon of identity crisis experienced by the Massenrempulu ethnicity in South Sulawesi. The Massenrempulu have long internally considered themselves an ethnicity, although outsiders do not widely recognize them as an ethnic group. This article is based on research on the topic of “The Emergence of the Massenrempulu Ethnicity in South Sulawesi,” which was an ethnographic study conducted in 2015. The research also included diverse sources such as the colonial notes by government employees of the Dutch East Indies held by the Royal Netherlands Institute of Southeast Asian and Caribbean Studies (KITLV) Jakarta. Through the application of a constructivist perspective, the socio-cultural complexity of Massenrempulu society can be explained in the historical context and understood as an ethnic group. Maspul people are an ethnicity in South Sulawesi in the same manner as the Bugis, Makassar, Luwuk, and Toraja. The Maspul ethnic group has consisted of three different subcultures, with their local histories, mythologies, and languages, which is understandable given the historical characteristics of the Maspul Federation.